EFFECT OF COMPRESSION WOOD ON SOME CHEMICAL PROPERTIES OF Pinus brutia Ten. LEANING TREES - Abdulrazak R. S. Almalah (Mesopotamia Journal of Agriculture)
This study was conducted to show the effect of compression wood on some chemical characteristics of brutia pine Pinus brutia Ten. trees growing naturally at Dohuk provenance and to compare it with the normal growing trees (tree leaning type) for four levels of stem height, and between compression wood and opposite wood present in front of compression wood (wood location) and between heart wood and sap wood (wood type) to know the possibility of using tree stems containing compression wood in various technological wood products. Results showed that all the highest percentage means of soluble extractives in etanol-benzen and hot water, lignin and ash percent were in the leaning trees compared to standing trees. Except of holocellulose which have the highest percent in the standing trees. It was noticed that there were decrease in soluble extractive percent and ash percent from stem base to stem top, the highest values for both characters were in the 1st height level (1.5m), then it decreased gradually by increasing height levels until it reached the lowest values at the 3rd height level (4.5m), then it increased slightly at the 4th height level (6m) ,except for ash content which decreased slightly. Lignin percent showed an increase by increasing height levels, by which lowest value of lignin percent was in the 1st height level (1.5m) and the highest value was in the 3rd height level (4.5m) then it decreased slightly at the 4th height level (6m). Holocellulose percent showed a reverse results compared to lignin percent, The results showed that the height mean values for most of chemical component were in the opposite wood except lignin percent which have the highest value in compression wood. Also, the highest chemical percent values were in heartwood, by which all soluble and insoluble extractive and ash increased in heartwood except holocelldose percent which have the highest value in sapwood. The results showed that the base of the leaning tree stem was eccentric, and it became more centric by increasing height level.